Study of urban edge for the intervention of informal settlements in the southwest periphery of Guayaquil - Seis, Luis; Quimi Bohorquez, Oswaldo Henry; Campoverde Tabara, Laura Marien; Plua Marcillo, Alfredo Javier; Briones Macias, Juan Carlos; Palacios Murillo, Jamil Ignacio (Eximia, 2023)
The urban fabric of Guayaquil is intertwined with the meanders of the Guayas River, where estuaries such as Puerto Lisa, as a scene of prone in-formal settlements on the banks of the estuary, have challenged urban planning and generated a negative impact on the environment and quality of life of their habitants. This article arises in response to the challenges posed by the invasion of estuaries due to informal construction practices, which have triggered a dis-parity between the urban environment and the ecosystem. We face the urgency of addressing this problem that has transcended local borders to become a glob-al phenomenon that affects developing cities. The Puerto Lisa estuary, located in the suburb of Guayaquil, has become an epicenter of these transformations, experiencing accelerated growth of settlements that challenge the sustainability and quality of life of its inhabitants. The relevance of this research lies in the search for strategies that make appropriate land use compatible, satisfying the needs of the community, and at the same time revitalizing the natural landscape of the Puerto Lisa estuary. It is a call to rethink urban planning, promoting sus-tainable development that harmonizes urban growth with environmental preser-vation. Throughout these pages, we will explore the current conditions of in-formal settlements, identify key challenges and problems, and propose a com-prehensive reorganization plan. It is concluded that the integration of the estu-ary generates integration of the public space of human settlements and promotes productive local development by articulating new regularized housing processes in safe areas of the estuary.